1981
DOI: 10.1126/science.7233238
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Baboons with Schistosoma mansoni Cercariae Attenuated by Gamma Irradiation

Abstract: Studies on the efficacy of a vaccine against schistosomiasis in young baboons (Papio anubis) disclosed that immunization with Schistosoma mansoni cercariae attenuated by gamma irradiation induced significant protection against subsequent infection with normal, viable S. mansoni cercariae. Such immunization resulted in reduced worm burdens (70 percent) and egg excretion rates (82 percent). These results support immunization as a potential method for schistosomiasis control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Baboons are excellent experimental models for human schistosomiasis (14)(15)(16)(17), including vaccine testing (18)(19)(20)(21). We found a reduction in the size of hepatic and intestinal granulomas in baboons infected after having been vaccinated, yet these smaller granulomas appeared to be fully effective in sequestering toxic egg products in the liver.…”
mentioning
confidence: 99%
“…Baboons are excellent experimental models for human schistosomiasis (14)(15)(16)(17), including vaccine testing (18)(19)(20)(21). We found a reduction in the size of hepatic and intestinal granulomas in baboons infected after having been vaccinated, yet these smaller granulomas appeared to be fully effective in sequestering toxic egg products in the liver.…”
mentioning
confidence: 99%
“…Our study shows that subtle lesions, including goblet-cell hyperplasia and villus atrophy, occur in the intestines of baboons infected by S. mansoni. The presence of these lesions could explain at least in part the clinical signs associated with acute schistosomiasis mansoni in the baboon, including malaise, anorexia, diarrhea, dysentery, and, occasionally, death (Stek et al 1981). The absorption of glucose and sorbital has also been shown to be impaired in S. mansoni-infected mice, probably due to apparent reduction of the total intestinal absorptive area (Vengessa and Leese 1979).…”
Section: Discussionmentioning
confidence: 99%
“…There are efforts to develop a vaccine against schistosomiasis. Radio-attenuated cercariae induced a high level of protection in animal models (Minard et al 1978 ;Stek et al 1981) and naturally resistant population groups exist (Correa-Oliveira et al 1989, which suggests that development of an effective vaccine is likely to be possible (McManus and Loukas, 2008). There is a list of recombinant proteins that correlate with resistance in human studies and/or have shown efficacy in animal models (McManus and Loukas, 2008).…”
Section: Introductionmentioning
confidence: 99%